A gilded trap in Dominican rice farming. (January 2019) - Cox, Michael; Payton, Frederick; Pimentel, Leoncio
Abstract: The Dominican rice sector is highly industrialized, with substantial levels of inputs and mechanization used to maximize the production of a rice monocultures. These practices have negative environmental effects and leave the sector ecologically and economically vulnerable. In this paper we identify barriers to and opportunities for pro-environmental change in the Dominican rice sector by applying the lens of path dependence to several of data sources. These include roughly two hundred in-person, structured interviews that our team conducted with rice farmers in the northwestern Dominican province of Montecristi, as well as key informant interviews with government officials involved in the agricultural sector there. The analysis proceeded in three steps. First, we descriptively analyzed the farmer interview data. Second, we developed a conceptual model of the rice commodity chain to identify other relevant actors in the system and the implications that these actors' roles and interests have for the future path of the system. Finally, we constructed a path dependence model and tested the applicability of the "gilded traps" scenario to explain the characteristics this model contains. We find that the Dominican rice sector can be characterized as a gilded trap, with the highly profitable industrial model driving farmer debt and vulnerability, and leaving them without substantial access to alternative technical assistance that departs from the goals and underlying assumptions of this model. We conclude by identifying the primary change factors that could disrupt the system, including local-level collective-action among farmers to join a group sustainable rice certification scheme, as well as the DR-CAFTA agreement that will lower tariffs and quotas on rice imports.